AL-GHILAH'S POLICIES AND PRACTICES IN THE PERSPECTIVE OF ISLAMIC LAW - Julianti Julianti (Universitas Islam Negeri (UIN) Mataram, 2020)
This research is motivated by the attention of the author who has studied a book of interpretation, namely the book